Rootstock mediated alteration in morphology and photosystem in sweet orange (Citrus sinensis) scion cv. Pusa Sharad under NaCl stress - KRIPA SHANKAR; O P AWASTHI; A K DUBEY; AWTAR SINGH; JAI PRAKASH; ARIA DOLATABADIAN (The Indian Journal of Agricultural Sciences, 2023)
There is a dearth of rootstock studies on how salinity stress imparts tolerance to the scion cultivar in citrus [Citrus sinensis (L.) Osbeck]. The impact of sodium chloride on sweet orange cv. Pusa Sharad (PS) grafted on 11 different rootstocks i.e. Jatti khatti (JK), X–639 (X9), CRH–12 (C12), NRCC–1 (N1), NRCC–2 (N2), NRCC–3 (N3), NRCC–4